MODE OF ACTION OF THE MAIN ANTI-PARASITIC DRUGS - Clare Vinaud, Marina; de Souza Lino Junior, Ruy (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Neglected tropical diseases affect more than 1 billion people in tropical and subtropical regions most of them are caused by parasites. Several of these diseases already have effective drugs capable of eliminating the causative parasite, however are not capable of interrupting the transmission cycle. This fact induces the continuous of repetitive treatments, which may result in the parasite’s resistance. This review aims to show the mechanism of action of the main drugs used to treat parasitic neglected tropical diseases in order to determine the drug’s target and help the understanding of how the parasites are killed within the host.